2001
DOI: 10.1038/sj.mp.4000830
|View full text |Cite
|
Sign up to set email alerts
|

Association of anorexia nervosa with the high activity allele of the COMT gene: a family-based study in Israeli patients

Abstract: Keywords: eating disorders; catechol-O-methyltransferase (COMT); polymorphism; haplotype relative risk (HRR); transmission disequilibrium test (TDT)Anorexia nervosa (AN) is a common, severe and disabling psychiatric disorder, characterized by profound weight loss and body image disturbance. 1 Family and twin studies indicate a significant genetic contribution 2,3 and pharmacological data suggest possible dysfunction of the serotonergic 4,5 and dopaminergic 6-9 pathways. Catechol-O-methyltransferase (COMT) is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 22 publications
(18 reference statements)
3
37
1
Order By: Relevance
“…Additionally, the COMT gene allele which is responsible for increased COMT activity has already shown an independent association with AN. 32 Prior to our previous study 10 it appeared that serotonin was the major neurotransmitter involved in AN. 4,5 However, integrating the results from our earlier study 10 with the findings described here, suggest important involvement of the noradrenergic system in the biological underpinnings of AN-R.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the COMT gene allele which is responsible for increased COMT activity has already shown an independent association with AN. 32 Prior to our previous study 10 it appeared that serotonin was the major neurotransmitter involved in AN. 4,5 However, integrating the results from our earlier study 10 with the findings described here, suggest important involvement of the noradrenergic system in the biological underpinnings of AN-R.…”
Section: Discussionmentioning
confidence: 99%
“…The Val158Met (rs4680) variant has been shown to significantly affect protein abundance and enzyme activity but not mRNA expression, suggesting that differences in protein integrity account for the difference in enzyme activity between alleles (Chen et al, 2004). Therefore, the Val108/158Met genetic polymorphism has been the subject of intense molecular epidemiologic study and has been reported to be associated with risk for a number of diseases including schizophrenia, obsessive-compulsive disorder, disordered cognitive abilities (for a review, see Bilder et al, 2004), anorexia nervosa (Frisch et al, 2001), anxiety (Enoch et al, 2003;McGrath et al, 2004), and drug abuse and alcoholism (Vandenbergh et al, 1997;Tiihonen et al, 1999;Horowitz et al, 2000;Kauhanen et al, 2000;Wang et al, 2001). However, many of these studies are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…However, only one of two studies involving AN and the Val158Met polymorphism in the COMT gene showed positive association with the allele that encodes a more active COMT variant. 27 The other study found no association with either allele. 28 Our findings may be important for treatment.…”
Section: Discussionmentioning
confidence: 83%